A social network-based intervention stimulating peer influence on children's self-reported water consumption: A randomized control trial. (1st August 2016) - Smit, Crystal R.; de Leeuw, Rebecca N.H.; Bevelander, Kirsten E.; Burk, William J.; Buijzen, Moniek
Abstract: The current pilot study examined the effectiveness of a social network-based intervention using peer influence on self-reported water consumption. A total of 210 children (52% girls; M age = 10.75 ± SD = 0.80) were randomly assigned to either the intervention ( n = 106; 52% girls) or control condition ( n = 104; 52% girls). In the intervention condition, the most influential children in each classroom were trained to promote water consumption among their peers for eight weeks. The schools in the control condition did not receive any intervention. Water consumption, sugar-sweetened beverage (SSB) consumption, and intentions to drink more water in the near future were assessed by self-report measures before and immediately after the intervention. A repeated measure MANCOVA showed a significant multivariate interaction effect between condition and time ( V = 0.07, F (3, 204) = 5.18, p = 0.002, pη 2 = 0.07) on the dependent variables. Further examination revealed significant univariate interaction effects between condition and time on water ( p = 0.021) and SSB consumption ( p = 0.015) as well as water drinking intentions ( p = 0.049). Posthoc analyses showed that children in the intervention condition reported a significant increase in their water consumption ( p = 0.018) and a decrease in their SSB consumption ( p < 0.001) over time, compared to the control condition ( p -values > 0.05). The children who were exposed to the intervention did not report a change in their water drinking intentions over time ( p = 0.576) whereas the nonexposed children decreased their intentions ( p = 0.026). These findings show promise for a social network-based intervention using peer influence to positively alter consumption behaviors. Trial registration: This RCT was registered in the Australian New Zealand Clinical Trials Registry (ACTRN12614001179628). Study procedures were approved by the Ethics Committee of the Faculty of Social Sciences at Radboud University (ECSW2014-1003-203). Highlights: We examined the effectiveness of an intervention using a social network approach and peer influence on children's water drinking behaviors. The intervention consisted of identifying and training the most influential children in each classroom to promote water consumption among their peers. Children who were exposed to the intervention reported an increase in their water consumption over time compared to the non-exposed children. The children exposed to the intervention also reported a decrease in their sugar-sweetened beverage consumption over time.